The morphology and preliminary phytochemistry of albizia saman (jacq.) F. mull (2003)
The morphology and phytochemistry of Albizia saman have been investigated. The leaflets are elliptic to oblong with attenuate to obtuse bases. The leaf apex is obtuse while the surface is glabrous with an entire margin. Epidermal cells are irregular to polygonal with straight to curved anticlinal walls on the adaxial surface. On the abaxial surface, the cells are polygonal with straight to slightly curved anticlinal walls. The leaves are hypostomatic with nnomocytic stomata. Trichomes are simple, unscriate and restricted to the abaxial surface of the leaf. Pollen grains arc large and stibprolate occurring either as monads occasionally or as polyads in most cases. Photochemical screening revealed the presence of alkaloids, cardiac glycosides and saponins in the leaf.